2009
DOI: 10.1002/jsfa.3753
|View full text |Cite
|
Sign up to set email alerts
|

Iron fortification and parboiled rice quality: appearance, cooking quality and sensory attributes

Abstract: BACKGROUND: Iron (Fe) fortification of parboiled rice increases both Fe concentration and bioavailability in milled grains (i.e. white rice). The aim of the present study was to evaluate parboiled rice fortified with 250 and 450 mg Fe kg −1 paddy rice for its pre-cooking appearance, cooking quality, basic sensory attributes and overall acceptance in comparison with unfortified parboiled rice in Thailand and local parboiled rice in Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 65 publications
3
22
1
Order By: Relevance
“…The results suggest that simultaneous fortification of Fe and Zn in parboiled rice had no negative impacts on Fe and Zn penetration into the inner layers of rice kernel and its retention after washing. However, the effectiveness of Fe and Zn penetration into the endosperm differed among the cultivars, probably due to their different physical and chemical properties as discussed previously 4,6,15 . It was found in the present study that cultivar SPR 1 and CNT 1 was more efficient in increasing Fe and Zn concentration in polished rice after fortification with Fe and Zn, compared with PSL 1, which was also observed in our previous studies on its individual fortification 6,8 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The results suggest that simultaneous fortification of Fe and Zn in parboiled rice had no negative impacts on Fe and Zn penetration into the inner layers of rice kernel and its retention after washing. However, the effectiveness of Fe and Zn penetration into the endosperm differed among the cultivars, probably due to their different physical and chemical properties as discussed previously 4,6,15 . It was found in the present study that cultivar SPR 1 and CNT 1 was more efficient in increasing Fe and Zn concentration in polished rice after fortification with Fe and Zn, compared with PSL 1, which was also observed in our previous studies on its individual fortification 6,8 .…”
Section: Discussionmentioning
confidence: 87%
“…However, a previous study reported that multi fortification of Fe with other minerals may cause undesired taste, colour and/or flavour because Fe reacts with several food ingredients and other minerals such as iodine, vitamin A, and other organic compounds 3,14 . However, our previous study reported that parboiled rice fortified with appropriate rates of Fe was acceptable among parboiled rice consumers, because it appeared similar or even better in appearance, cooking quality, and sensory attributes than local parboiled rice 15 . In the present study, doubly-fortified rice was also found to have similar physical properties as those of the singly-fortified rice, but the cooking quality and sensory attributes would need to be tested.…”
Section: Discussionmentioning
confidence: 93%
“…Rice fortification, for instance, may lead to an intensification of color, which negatively affected its acceptability in Thailand and Bangladesh 128 . With respect to Golden Rice, the visible differences between this GM biofortified rice crop and its regular counterpart could be a constraint to consumer acceptance, because its yellow color may be linked with a longer shelf life and, thus, lower quality.…”
Section: Key Challenges Of the Commercialization Of Gm Biofortified Ricementioning
confidence: 99%
“…The "Flavr Savr" tomato, for instance, was primarily intended to increase its shelf life, but is also characterized by an improved flavor (Kramer and Redenbaugh, 1994). Also iron fortification of rice can change the initial flavor and chewiness (Prom-u-thai et al, 2009). According to the International Food Information Council (IFIC) study in 2001, about 58% of US consumers indicated that they would like to purchase products which have been modified to taste better (IFIC/Wirthlin, 2001).…”
Section: Gm Food Attributes and Consumer Acceptancementioning
confidence: 99%
“…Stevens and Winter-Nelson (2008) however, found negative reactions to the flavor and aroma of provitamin A-biofortified maize, which is expected to influence consumer acceptance (Hossain et al, 2003). Product attributes related to preserving and processing GM food, such as the shelf life, and the duration and the sensory quality of cooking, could also play a role (Bonti-Ankomah and Yiridoe, 2006;De Groote and Kimenju, 2008;Prom-u-thai et al, 2009). …”
Section: Gm Food Attributes and Consumer Acceptancementioning
confidence: 99%